The past, present and future of the EU’s federal experience - Coutinho, Francisco Pereira; Pires, Martinho Lucas (Perspectives on Federalism, 2018)
In 2017 we celebrated the 60th anniversary of the Treaty of Rome and the 25th anniversary of the Treaty of Maastricht. The commemoration of these historic events was the perfect excuse for a critical and renewed discussion of European integration. It was also an opportunity for discussing the EU through the lens of “federalism”, i.e. to look at it from the perspective of federal theory and / or through its substantive and formal dimension. This issue of Perspectives on Federalism includes papers presented in conferences organized at Warsaw University in June 2016 and at Lisbon Nova Law School on May 2017 under the Jean Monnet Project “More EU - More Europe to Overcome the Crisis”. The articles discuss, either from a more general or from a more specific standpoint, within a variety of subjects, some of the federal features of the EU.